Species diversity and seasonal dynamics of filamentous cyanobacteria in urban reservoirs for drinking water supply in tropical China - Yang, Yang (Ecotoxicology (London, England), 2020)
Filamentous cyanobacteria have been observed to become the dominant species in reservoirs, especially in small reservoirs for drinking water supply in southern China. The occurrences of filamentous cyanobacteria blooms in such reservoirs add additional costs for water plants by decreasing the filtration efficiency and the potential of toxin production. To serve the purpose of drinking water supply, the effective risk assessment requires the dynamic pattern of filamentous cyanobacteria. This study seasonally collected samples from 25 reservoirs in Dongguan, one of the most important 'world factories' in China in July, December and March, and investigated the temporal dynamics of phytoplankton, particularly cyanobacteria community. Our investigation showed that filamentous cyanobacteria, Planktothrix sp, Limnothrix sp. and Cylindrospermopsis raciborskii dominated in these reservoirs and climate-related water temperature was the primary factor for the seasonal shift of filamentous cyanobacteria. High abundance of filamentous cyanobacteria occurred in the high water level period with increasing temperature but less relevant with nutrient conditions. Our study observed the seasonal dynamics of filamentous cyanobacteria in tropical urban reservoirs and highlighted the association between temperature and filamentous cyanobacteria. our data and analysis provided an evidence that increased temperature could increase the likelihood of frequency and intensity of filamentous cyanobacteria blooms. In the scenario of global warming, more frequent monitoring of filamentous cyanobacteria and the potential to produce toxin should be considered for water quality and reservoir management